Anti-inflammatory Constituents from Branches of Corylus hallaisanensis Nakai - Sung Chun Kim , , Ha Na Ko,Chang-Gu Hyun, Jong Seok Baik, Hee Jung Bu, Nam Ho Lee (Journal of Applied Pharmaceutical Science, 2015)
Development of bioactive ingredients from natural sources has long been the research project of our laboratory. In this study, the extract from Corylus hallaisanensis Nakai branches was investigated and their anti-inflammatory constituents were identified. The prepared ethanol extract was successively partitioned into n-hexane, ethyl acetate, n-butanol and aqueous layers. Upon anti-inflammatory screenings, ethyl acetate fraction exhibited good nitric oxide production inhibitory activity in lipopolysaccharide-induced RAW 264.7 cells. Further phytochemical studies for the ethyl acetate fractions led to isolation of four constituents such as β-sitosterol (1), 3,3’,4’-tri-O-methylellagic acid (2), carpinontriol A (3) and carpinontriol B (4). All of the compounds were isolated for the first time from this plant. The isolates 2, 3 and 4 showed considerable inhibition on the production of nitric oxide in the RAW 264.7 cell without causing cell toxicities. And compounds 3 and 4 reduced the production of interleukin-6, an inflammatory cytokine, in dose-dependent manner in RAW 264.7 cells. Based on these results, C. hallaisanensis extracts could be potentially applicable as anti-inflammatory agents in pharmaceutical or cosmetic industries.
Keywords: Corylus hallaisanensis, anti-inflammation, RAW 264.7 cell, isolation, carpinontriol A.